Effectiveness of In-Person and Virtual International Mobility Scholars Programme on Career and Professional Development - Alexis Carr; Catherine Beaudry (Journal of Learning for Development, 2023)
International mobility programmes, both in-person and virtual, aim to build human capital. Though there is evidence of their impact on skill development, there is scant research on career and professional benefits. Moreover, because virtual mobility is a new concept, there has been little investigation into how this mode affects the perceived benefits. Using the lens of human capital theory, this study explores outcomes of in-person and virtual mobility in the Queen Elizabeth Scholars-Advanced Scholars programme, which includes doctoral, post-doctoral and early career scholars. Through interviews with 23 scholars, we explore the perceived impact of the programme, considering mode of delivery, on the career and professional development of scholars. Despite challenges with the unexpected shift to virtual mobility during Covid-19 lockdowns, both in-person and virtual mobility scholars reported benefits to their career and professional development. These results suggest that virtual mobility may be considered as a viable option to enhance the flexibility, inclusivity, and accessibility of such programmes.